Patient-reported outcomes and morbidity after head and neck reconstructions: An evaluation of fibular and scapular free flaps. (September 2022) - Liu, Alice Q.; Deane, Emily C.; Heffernan, Austin; Ji, Yunqi; Durham, J. Scott; Prisman, Eitan
Highlights: Review of patient-reported outcomes and morbidity with osteocutaneous free flaps. Patients had more donor site morbidity after fibula free flaps. Scapula free flap patients had less early peri -operative morbidity. Both scapula and fibula free flaps reported mild decision regret. No difference in major complications between groups. Abstract: Background: Fibular (FFF) and scapular free flaps (SFF) are versatile tissue transfers for head and neck reconstruction. However, their relative morbidity has been sparsely studied. The primary goal of this study was to evaluate the morbidity and patient-reported outcome measures of these two reconstructive options. Materials and Methods: Case series of patients from 2017 to 2020 who underwent a FFF or SFF for head and neck ablation. Demographic and surgical outcome measures, such as Charlson Comorbidity Index (CCI), anesthetic time, donor site morbidity, and perioperative morbidity score (POMs) were extracted. Patients were contacted to complete the Decision Regret Scale (DRS), University of Washington Quality of Life (UW-QoL), Oral Health Impact-14, and limb specific functional outcome measures. Statistical analyses included a linear regression. Results: In total, 97 FFF (mean age 58.5, 62.9% male) and 55 SFF (mean age 64.8, 63.6% male) were included. Total surgical time was higher in the SFF group (p < 0.05) and they had more comorbidities (p < 0.01). SFF patients had lower POM scores on post-operative day three (p < 0.05) while FFF patients scored better on the UW-QoL Physical Domain (p < 0.01). The DRS for both groups (FFF mean DRS 22.7, SFF mean DRS 19.2) was similar. When adjusted for patient morbidity, however, the SFF group had less decisional regret (p < 0.05). Conclusion: This is the largest comprehensive evaluation of patient-reported outcome measures for FFF and SFFs. SFFs required longer surgical times but had less early morbidity than FFFs. Patients who underwent either reconstructions reported mild decisional regret, proving these are generally well tolerated procedures.